2014
DOI: 10.1097/aud.0b013e3182a6ca91
|View full text |Cite
|
Sign up to set email alerts
|

Rotatory and Collic Vestibular Evoked Myogenic Potential Testing in Normal-Hearing and Hearing-Impaired Children

Abstract: The observed pediatric age correlations underscore the necessity of age-appropriate normative data to guarantee accurate interpretation of test results. The high percentages of abnormal vestibular test results in hearing-impaired children emphasize the importance of vestibular assessment in these children because the integrity of the vestibular system is a critical factor for motor and psychological development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
80
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(85 citation statements)
references
References 58 publications
3
80
0
2
Order By: Relevance
“…For example, it has been demonstrated that up to 70% of children with sensorineural hearing loss have some degree of vestibular end-organ dysfunction [19], and that the prevalence of dysfunction is higher in children with profound hearing loss [20]. More recently, rotatory and collic Vestibular Evoked Myogenic Potential abnormalities have been described in children with sensorineural hearing loss compared to healthy peers [21][22][23]. These findings may seem discordant from ours, but in the above mentioned studies the cohort with hearing loss included several cases of Pendred syndrome, enlarged vestibular aqueduct and other cochlear malformations, together with cases of post-meningitis and Cytomegalovirus-related hearing loss.…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…For example, it has been demonstrated that up to 70% of children with sensorineural hearing loss have some degree of vestibular end-organ dysfunction [19], and that the prevalence of dysfunction is higher in children with profound hearing loss [20]. More recently, rotatory and collic Vestibular Evoked Myogenic Potential abnormalities have been described in children with sensorineural hearing loss compared to healthy peers [21][22][23]. These findings may seem discordant from ours, but in the above mentioned studies the cohort with hearing loss included several cases of Pendred syndrome, enlarged vestibular aqueduct and other cochlear malformations, together with cases of post-meningitis and Cytomegalovirus-related hearing loss.…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…It is known that the prevalence of vestibular test abnormalities is higher in profound sensorineural hearing loss (Selz et al 1996;Tribukait et al 2004;Maes et al 2014), in acquired deafness (meningitis and labyrinthitis) (Selz et al 1996;Tribukait et al 2004;Cushing et al 2009), and in some syndromes associated with deafness such as in Charge (Abadie et al 2000), Usher (Teschner et al 2008), Waardenburg (Black et al 2001), and Pendred (Luxon et al 2003) syndromes. Vestibular dysfunction is rather rare in deafness caused by mutations in the GJB2 gene, encoding connexin 26 (Denoyelle et al 1999;Nickel & Forge 2008;Weegerink et al 2011).…”
Section: Introductionmentioning
confidence: 97%
“…Following the observed benefits of bilateral CI, more children with a hearing loss are implanted bilaterally. Although cochlear implantation can be regarded as a safe surgical procedure in general, bilateral CI is associated with a higher risk of vestibular damage and consequently higher risk of vestibular complaints such as vertigo or instability in comparison with unilateral implantation (Enticott et al 2006;Licameli et al 2009;Wagner et al 2010;Maes et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis and interpretation of vestibular tests are challenging, due to difficulties with cooperation, maintenance of alertness, and nauseating reactions. Therefore, the implementation of a test protocol for children with normative data at appropriate ages is of great importance in vestibular assessment (5) . There is no standard defined in the graphical findings of the current vestibular exams considered normal for the different pediatric age groups, making it more difficult to characterize normal and pathological results.…”
Section: Introductionmentioning
confidence: 99%